Feeding Ensiled Citrus Pulp to Finishing Pigs - J. D. Crosswhite; N. B. Myers; Adegbola T. Adesogan; Joel H. Brendemuhl; Dwain D. Johnson; Chad C. Carr (EDIS)
For the past six years, feed costs have continually increased, and Florida has greater feed costs than the rest of the country because grain must be shipped here from where it was produced. But the Florida pork producers generally get prices above market value for their pigs because of strong demand for locally raised foods. These Florida pork producers could become more profitable if they could significantly decrease their production costs. In Florida, pork producers have an opportunity to use citrus byproducts as a feedstuff to substantially and sustainably decrease their feed costs. This 4-page fact sheet was written by J. D. Crosswhite, N. B. Myers, A. T. Adesogan, J. H. Brendemuhl, D. D. Johnson, and C. C. Carr, and published by the UF Department of Animal Sciences, August 2012.